Review of Economic Studies Travel Fund (Review of Economic Studies, 1989)
Journal Article Review of Economic Studies Travel Fund Get access The Review of Economic Studies, Volume 56, Issue 4, October 1989, Page 475, https://doi.org/10.2307/restud/56.4.475-a Published: 01 October 1989